A New Look at Space - Muminovich Khadjibaev , Abduhakim (New Trends in Physical Science Research Vol. 1, 2022)
Among all the fundamental categories of physics, space is the dominant place, for everything that exists as a physical reality. Until the end of the 19th century the prevailing consensus was that there was a continuous “environment” called “ether” that fills all space, but completely intangible for humans. After the experiments of Michelson and Morley and describing the principles of Einstein’s Special Theory of Relativity, the concept of “ether” was completely discarded from science. It was recognized, that electromagnetic waves propagate in an absolute vacuum. With the advent of the General Theory of Relativity and quantum mechanics, the need to recognize the presence of a certain "medium" filling space reappeared. Such concepts as “physical field”, “physical vacuum”, scalar field (Higgs field) and others were proposed. The author in this article proposes the concept according to which space-time is considered as the physical system that consists of physical substrate and presents itself as an “absolute physical reality”.